From language to culture... through words (مجلة إحالات, 2026)
The relationship between a language and its culture cannot be questioned. Language conveysa representation of the world and expresses a reality that differs according to cultures. It’s not just atool for communication, because it generates symbolic relationships that shape people'srepresentations and worldviews. Our choice of words isn’t random, but rather reflects our thinkingand the world in which we live. Languages express the same things in different ways. To reachculture, language is the best means because it’s a transmitter, product, and producer of cultures. Theresearch aims to emphasize the necessity of working on vocabulary to present everyday culture,through examples that illustrate this close relationship between language and culture.